Mycophenolate Mofetil for the Treatment of Autoimmune Hepatitis in Patients Refractory to Standard Therapy - Shane M Devlin; Mark G Swain; Stefan J Urbanski; Kelly W Burak (Canadian Journal of Gastroenterology)
There are limited therapeutic options available for patients with autoimmune hepatitis in whom conventional treatment fails. A case series of five patients unresponsive to or unable to take azathioprine, 6-mercaptopurine or corticosteroids who were treated with mycophenolate mofetil (MMF) is reported. While on MMF, alanine aminotransferase normalized or remained normal in all patients. MMF had a steroid-sparing effect and histological remission was demonstrated in one patient after seven months of MMF. One patient experienced an uncomplicated episode of pyelonephritis. In conclusion, MMF can effectively induce and maintain remission in refractory autoimmune hepatitis patients.